Adverse Events, Length of Stay, and Readmission After Surgery for Tibial Plateau Fractures. Issue 3 (March 2015) - Basques, Bryce A.; Webb, Matthew L.; Bohl, Daniel D.; Golinvaux, Nicholas S.; Grauer, Jonathan N.
Abstract : Objectives: To identify factors that are associated with short-term outcomes after open reduction and internal fixation (ORIF) for tibial plateau fracture. Methods: Patients who underwent ORIF for tibial plateau fracture from 2009 to 2012 were identified in the American College of Surgeons National Surgical Quality Improvement Program database. Patient characteristics were tested for association with any adverse event (AAE), severe adverse events (SAEs), infectious complications, extended length of stay (LOS), and readmission within 30 days. Results: A total of 519 tibial plateau fracture patients met inclusion criteria. Ten percent had AAE, 7% had SAEs, and 4% had an infectious complication. Extended LOS was defined as LOS >3 days (75th percentile LOS). Four percent of patients were readmitted. AAE was associated with increased American Society of Anesthesiologists (ASA) class [relative risk (RR) = 3.8] and history of pulmonary disease (RR = 2.1) on multivariate analysis. SAE was associated with male sex (RR = 2.2) and increased ASA class (RR = 3.6). Infectious complications were associated with male sex (RR = 3.0), increased ASA class (RR = 3.3), smoking (RR = 2.8), pulmonary disease (RR = 2.9), and bicondylar fracture (RR = 2.7). Extended LOS was associated with increased age (RR = 2.1), increased ASA class (RR = 2.0), diabetes (RR = 1.6), pulmonary disease (RR = 1.8), bicondylar fracture (RR = 1.6), and increased operative time (RR = 1.6). Readmission was associated with increased ASA class (RR = 3.9), diabetes (RR = 2.9), dependent functional status (RR = 8.1), and discharge to home (RR = 5.7). Conclusions: The above-identified factors associated with outcomes after ORIF for tibial plateau fracture may be useful for patient counseling. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.